LITERATURE REVIEW: THE EFFECT OF PBL MODEL ON STUDENTS’ PROBLEM SOLVING SKILLS - A.C, Prawita; A., Muttaqiin; R.E., Putri (ISER (Indonesian Science Education Research), 2024)
This study aims to examine the effect of PBL model on students' problem solving ability. The form of this research is a literature review. The data collection technique is sourced from secondary data collected based on the keyword influence of the PBL model on students' problem solving skills, published articles with a range of years 2014-2024 obtained from google scholar. The amount of data obtained is 10 articles that meet the criteria for further review. Based on the results of the study of the 10 articles obtained, it was found that: 1) the PBL model can improve students' solving ability, 2) there is a significant difference when using the PBL model compared to using conventional and expository models, 3) in addition to improving problem solving ability, the PBL model can also improve science process skills, critical thinking skills and student learning outcomes, 4) the average score in the experimental class is higher than the control class. 5) in supporting the success of the PBL model during the learning process, other media can be used.   Keywords: PBL, model, problem, solving, ability